Mona Lisa smile - Goldsmith-Thomas, Elaine; Schindler, Deborah; Schiff, Paul; Konner, Lawrence; Rosenthal, Mark D.; Newell, Mike 1942-; Roberts, Julia 1967-; Dunst, Kirsten 1982-; Stiles, Julia 1981-; Gyllenhaal, Maggie 1977-; Stevenson, Juliet; West, Dominic 1970-; et al. (Columbia TriStar Home Entertainment, 2004)
Set in 1953, Katherine Watson is a free-spirited graduate of UCLA who accepts a teaching post at Wellesley College, a women-only school where the students are torn between the repressive mores of the time and their longing for intellectual freedom.